PROSES POLITIK BERLAPIS DALAM GERAKAN RESTORASI SUNGAI - Siti Zunariyah; Suharko Suharko; Suharman Suharman (Jurnal Analisa Sosiologi, 2022)
This article discusses river restoration movement through analytical frame of multilayered political process of river restoration movement. River restoration movement is very important to study, not only because of limited social science literature on this theme, but also because of the uniqueness of movement dynamic from one region to another. Method selected was an explanatory case study to explain the multilayered political process occurring in river restoration movement conducted by Forsidas Gajah Wong Yogyakarta. The first layer is base or grassroots of movement becoming an important keyword to be tipping point of the movement by building common consciousness of the urgency to recover degraded river. The process of consolidation and of building shared point of view is an unforgettable part despite spatial-scale implementation. The second layer consists of policy maker elites and central actors serving as the activator of the support raising process at either executive or legislative level. In addition, building social network between river communities reinforce the processes at base and elite levels. The procedure of movement is as follows: (1) preparing the people socially by means of building common consciousness and equating the perspectives among the people living in the river bank; (2) building consolidation between the people living in the river bank connected spatially to each other through Forsidas Gajah Wong institution; (3) raising support, lobby, and advocacy from policy makers including executives and legislatives to contribute to the process of organizing settlement along the river and rubbish and waste processing facility to reduce river degradation rate; (4) joint action constitutes mutual cooperation (gotong royong) and selfhelp in the attempt of restoring river ecosystem; and (5) reflection and movement evaluation processes. The important contribution of current research is related to the importance of multilayered political process in the procedure and the dynamic of river restoration movement. Keywords: River Restoration Movements, Multilayered Political Process and Social Networks AbstrakArtikel ini adalah tentang gerakan restorasi sungai melalui kerangka analisis proses politik berlapis gerakan restorasi sungai. Gerakan restorasi sungai sangat penting untuk dikaji, tidak hanya karena minimnya literatur ilmu sosial dalam tema ini, namun juga karena keunikan dinamika gerakan dari satu wilayah dengan wilayah lainnya. Metode yang dipilih adalah studi kasus yang bersifat eksplanatoris untuk menjelaskan proses politik berlapis yang terjadi pada gerakan restorasi sungai yang dilakukan oleh Forsidas Gajah Wong Yogyakarta. Lapis pertama adalah lapis basis atau grassroot gerakan menjadi kata kunci penting untuk menjadi titik ungkit gerakan dengan membangun kesadaran bersama tentang urgensi memulihkan kembali sungai yang terdegradasi. Proses konsolidasi dan membangun kesamaan cara pandang menjadi bagian yang tidak terlupa meskipun dilakukan dalam skala spasial. Lapis kedua adalah lapis elit pengambil kebijakan dan peran aktor sentral yang menjadi motor penggerak dalam proses menggalang dukungan baik pada jalur eksekutif maupun legislative. Selain itu, membangun jejaring sosial antar komunitas sungai menjadi penguat proses-proses pada level basis dan level elit. Tahapan gerakan ini yaitu; (1) melakukan persiapan sosial masyarakat dengan cara  membangun kesadaran bersama dan menyamakan cara pandang antar warga bantaran sungai; (2) melakukan konsolidasi antar warga bantaran sungai yang terhubung secara spasial antar wilayah sungai dalam wadah Forsidas Gajah Wong; (3) menggalang dukungan, lobby dan advokasi dari para pengambil kebijakan dari unsur eksekutif dan legislative untuk berkontribusi dalam proses penataan pemukiman sepanjang sungai dan sarana pengolahan sampah dan limbah agar mengurangi laju degradasi sungai; (4) aksi bersama berupa gotong royong dan swadaya dalam rangka restorasi ekosistem sungai; dan (5) proses refleksi dan evaluasi gerakan.  Kontribusi penting penelitian ini adalah pentingnya proses politik yang berlapis dalam tahapan dan dinamika gerakan restorasi sungai. Kata Kunci: Gerakan Restorasi Sungai, Proses Politik Berlapis dan Jejaring Sosial